Deliberative democracy as a critical theory. Issue 7 (10th November 2019) - Hammond, Marit
Abstract: Deliberative democracy's roots in critical theory are often invoked in relation to deliberative norms; yet critical theory also stands for an ambition to provoke tangible change in the real world of political practice. From this perspective, this paper reconsiders what deliberative democracy ought to look like as a critical theory, which has not just theoretical and practical, but also methodological implications. Against conceptions of activism as pushing through one's pregiven convictions, recent debates in critical theory highlight the necessity for critical activism to be emancipatory in way that is enabling rather than imposing, and inclusive rather than 'enlightened'. As such deliberative democracy must be at once a critical theory of democracy and a democratic critical theory: committing itself to being an innately inclusive, itself reflexive and self -reflexive project rather than a substantive theory to be implemented.